Kedatuan Luwu: Nilai-Nilai To Accana Luwu - Yunus Yunus; Mukhoyyaroh Mukhoyyaroh (Muqoddima Jurnal Pemikiran dan Riset Sosiologi, 2021)
This study aims to describe the value of To Ciung Maccae Ri Luwu. The research uses library research method by understanding books related to To Ciung Maccae Ri Luwu. Datu Luwu named Datu Etenriawe (1581-1611), known as a statesman and scholar who gave a lot of attention to the condition of kedatuan. His name is Tociung. Tociung gave many ideas or thoughts and messages to the kedatuan/government which aimed to maintain the continuity of the kingdom, so that the kedatuan avoided destruction. The unanimous union is interpreted, that all problems that exist in the country or country are faced together, both in terms of bad and in terms of goodness. Then the union is like a round of rice, interpreted as a vertical union is the union between the king or leader and his people, so that what is the greatness of the king, will become strength for the servant. The integration of the eight characteristics among the leader and the community, would invoke unity in the community. The state or country will be strong, and resistant to outside interference. Then there are several kinds of unity according to Maccae ri Luwu’s thought, namely “united like a chicken egg, united like rice, and united like a bamboo reed”.